PENERAPAN MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION BERBANTUAN MEDIA LEAFLET DILENGKAPI LKS WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 1 NGGAHA ORI ANGU - Tanggu Hana, Yulensi; Makaborang, Yohana; Rmbu Hada Enda, Riwa (Universitas Cokroaminoto Palopo, 2025)
This study aims to provide a comprehensive overview of the implementation of the cooperative learning model Group Investigation assisted by leaflet media and complemented with Word Square worksheets, as well as to describe the improvement in students' learning outcomes after applying the model and learning media. This research is a Classroom Action Research (CAR) using a descriptive quantitative approach. The subjects of this study were eighth-grade students at SMP Negeri 1 Nggaha Ori Angu. Data collection instruments included observation sheets and written tests. The results of the study showed a significant improvement in cognitive learning outcomes, from 24% in the pre-cycle to 72% in cycle I, and further increased to 84% in cycle II. Meanwhile, affective learning outcomes also improved, from 28% in cycle I to 88% in cycle II. Therefore, it can be concluded that the application of the cooperative learning model Group Investigation assisted by leaflet media and complemented with Word Square worksheets can improve the learning outcomes of eighth-grade students at SMP Negeri 1 Nggaha Ori Angu.